Sexual behaviors in Mexican youth during COVID-19 confinement - Amaro-Hinojosa, Marily Daniela (Universidad de Sonora, 2020)
Introduction: Confinement due to the coronavirus pandemic (COVID-19) caused changes in sexual and reproductive health care, as well as in the sexual behaviors of the population. Objective: Describe the sexual behaviors of young Mexicans during COVID-19 confinement. Methodology: Cross-sectional descriptive design, where the sample consisted of 613 Mexican young people ranging from 18 to 28 years of age; sampling was non-probabilistic by convenience, an online survey was conducted. A data questionnaire and a sexual behavior questionnaire adapted for this study were applied. Data analysis was performed with the SPSS version 25 statistical package, using descriptive and inferential statistics such as Student's t-test. Results: The main behaviors found during coronavirus confinement were the following: Masturbation 49.9%, viewing pornography 43.2%, sexting 33.9%, cybersex 17.9% and oral, vaginal, and/or anal sex 46.8%. Conclusions: Youth sexual behavior changed during confinement compared to the former year. These findings provide evidence for the implementation of nursing interventions for the promotion of sexual health during health crisis situations such as COVID-19.